The Impact of Oxford Nanopore Technologies Based Methodologies on the Genome Sequencing and Assembly of Romanian Strains of Drosophila suzukii - Attila Cristian Ratiu; Adrian Ionascu; Nicoleta Denisa Constantin (Insects)
Background: Drosophila suzukii is a worldwide invasive species with serious economic impacts. Herein, we are presenting the first project of sequencing and assembling the whole genomes of two lines of D. suzukii derived from Romanian local populations using exclusively Oxford Nanopore Technologies data. Methods: We implemented both MinION and Flongle flow-cells and tested the impact of various basecalling models and assembly strategies on the quality of the sought-after representative genome assemblies. Results: We demonstrate that the sup-basecalling model significantly improved the read quality and that adding a relatively small collection of reads had a significant positive impact over the assembly quality. The novel dScaff bioinformatics prototype tool allowed us to perform sequence-level quality tests, as well as to represent assembly selections and display both the contig redundancy and the repeats-enriched genomic sub-sequences. Moreover, we used dScaff to propose a minimal assembly variant corresponding to one of our lines, GB-ls-coga4, which assured a basic linear coverage of the genome and exhibited quality parameters comparable with those particular to the current reference genome assembly. Conclusions: The study presents the first sequencing and assembly of a D. suzukii line in Romania and argues the efficiency of long-read sequencing strategies.